STRATEGI PEMBENTUKAN KARAKTER SISWA PADA JENJANG PENDIDIKAN DASAR MELALUI MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Akhmad Aji Pradana (PREMIERE : Journal of Islamic Elementary Education, 2021)
The rapid development of science , knowledge , technology and information systems make the impact positive and negative impact on education world. An effort to reduce the negative effect of technology appliance on education is by applying character-based education on the Elementary school students. As part of the Elementary School curriculum, a lesson called Physical Education indirectly have focus to develop the character of overall. In order to optimize the character of students through physical education, required several studies about strategy in developing character of students learning through it. Thus, this articles aims to discuss: character based education, physical education as part of character education, strategy of developing the students character through physical education learning. This article using library research as research type. In this research, researchers collected data from various sources contained on news and articles from online journal. The selected criteria of the articles used in this research which have relevant discussion of character-based education, physical education as part of character education, strategy of developing the students character through physical education learning. The conclusions can be described is: 1. The students character shaping through character based education can be optimized on Elementary School Level but keep paying attention on some priciples including: Universal moral values; holistic; integrated; participatory; local wisdom; the XXI century skills; fair and inclusive; suitable with students development; and measurable. 2. The character shaping of Elementary School students can be optimized by physical education through continuous process, correct learning methods, and suitable technic and strategy. 3. The character shaping of Elementary School students through physical education can be doing with inclusive strategy.